Análisis de las consecuencias de la aplicación del código de trabajo al sector doméstico en la ciudad de Latacunga durante el período de julio a diciembre 2011 - Ruiz Plasencia, Mayra Carolina (2013)
The general objective of this work investigative was, to determine the consequences of any use of working code domestic sectoring the city of Latacunga, Cotopaxi Province, in order to establish clearly the problematic between employer and domestic service workers; The type of research used in the current study is the descriptive method which described the external environment of the domestic workers to establish a situational diagnosis to collect enough information about social security, job fair remuneration which is embedded in domestic workers. Additionally, the descriptive method outlined common features in order to identify the problem which has arisen in this sector, for example the unwarranted dismissals, work without prior legalization, etc. The application of techniques such as: surveys were an essential tool to obtain required information to do an analysis about what has been happening with the domestic workers since the adoption of the law which allows them to receive a fair salary.